C646, a Novel p300/CREB-Binding Protein-Specific Inhibitor of Histone Acetyltransferase, Attenuates Influenza A Virus Infection - Zhao, Dongming; Fukuyama, Satoshi; Sakai-Tagawa, Yuko; Takashita, Emi; Shoemaker, Jason E.; Kawaoka, Yoshihiro (Antimicrobial agents and chemotherapy, 2016)
New strategies to develop novel broad-spectrum antiviral drugs against influenza virus infections are needed due to the emergence of antigenic variants and drug-resistant viruses. Here, we evaluated C646, a novel p300/CREB-binding protein-specific inhibitor of histone acetyltransferase (HAT), as an anti-influenza virus agent in vitro and in vivo and explored how C646 affects the viral life cycle and host response. Our studies highlight the value of targeting HAT activity for anti-influenza drug development.